Morpho-anatomy and HPTLC Profiling of Senna Mill. Seeds Used in Traditional System of Indian Medicine - Radha P; Divya KG; Udhayavani C; Murugammal S; Shakila R; Sunil Kumar KN (Pharmacognosy Research, 2023)
Background: The present study was carried out to compare macro-microscopy, powder microscopy and HPTLC analysis of six species such as Senna auriculata (L.) Roxb., Senna alata (L.) Roxb., Senna alexandrina Mill., Senna occidentalis (L.) Link., S. uniflora (Mill.) Irwin and Barneby, S. tora (L.) Roxb. of the genus Senna Mill. belongs to the family Caesalpiniaceae. Materials and Methods: Six selected Senna species were collected, shade dried and pharmacognostic study were performed used techniques such as microscopy and HPTLC analysis. Results: Seed macro-morphology of the selected six species shows significant variations in size, shape, colour, ornamentation and number of seeds per pod. The basic cellular structure of six Senna species was anatomically similar but variation was observed in number of layers. Microscopic characters of the selected species revealed key diagnostic features that can help to determine the relationship between the closely related species; macrosclerieds and osteosclerdies were observed in Senna auriculata and S. occidentalis. Powder microscopy of selected six Senna species varied in colour, texture and odour. Numerous rosette crystals in cotyledonary cells were found only in Senna tora which is a significant variation from other five Senna species. HPTLC finger print profiling was performed with ethanol extract at 254 nm, 366 nm and 575 nm derivatization using vannilin-sulphuric acid and the results were documented. In 254 nm 14 bands were separated but the major peak at Rf 0.31 (22.24%) appeared in S. alexandrina. Conclusion: A detailed morphological and pharmacognostical evaluations play an important role to avoid misidentification and delimitation of selected six Senna species and HPTLC profiling is an additional analytical tool for species identification.
Keywords: anatomy.; S. alata; S. alexandrina; S. auriculata; S. occidentalis; S. tora; S. uniflora; Senna